2001
DOI: 10.1111/j.1095-8312.2001.tb01388.x
|View full text |Cite
|
Sign up to set email alerts
|

Pectoral fins of rhizodontids and the evolution of pectoral appendages in the tetrapod stem-group

Abstract: The Rhizodontida are an extinct order of large, predatory, lobe-finned fishes, found world-wide in Devonian and Carboniferous freshwater deposits. They are thought to be basal members of the tetrapod lineage. In this paper the pectoral fin skeleton of Rhizodus hibberti, a derived member of the group, is described in detail for the first time. It shows that muscular processes of the humerus (the deltoid and supinator processes) may have appeared later in tetrapod evolution than previously thought. The rhizodont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 48 publications
(76 reference statements)
1
29
0
Order By: Relevance
“…In Barameda, this depression has striations interpreted as muscle attachment scars (Garvey et al, 2005). Jeffery (2001) also suggested that the deltoid and supinator processes identified by Long (1989) in Barameda may be part of a continuous dorsal ridge, as in Rhizodus, and Garvey et al (2005) do not disagree with this position, noting that continuous ridges are present in Aztecia and Sauripterus, although their orientation is somewhat different. In Gogonasus, Holland (2013) described a deltoid process that was 'rounded, moderate in size, and is marked with scars for muscle attachment' and, distally, a 'large supinator process, which is pointed and marked with a small circular area of unfinished bone' (p. 156).…”
Section: (B) Tetrapodomorph Fishmentioning
confidence: 99%
See 4 more Smart Citations
“…In Barameda, this depression has striations interpreted as muscle attachment scars (Garvey et al, 2005). Jeffery (2001) also suggested that the deltoid and supinator processes identified by Long (1989) in Barameda may be part of a continuous dorsal ridge, as in Rhizodus, and Garvey et al (2005) do not disagree with this position, noting that continuous ridges are present in Aztecia and Sauripterus, although their orientation is somewhat different. In Gogonasus, Holland (2013) described a deltoid process that was 'rounded, moderate in size, and is marked with scars for muscle attachment' and, distally, a 'large supinator process, which is pointed and marked with a small circular area of unfinished bone' (p. 156).…”
Section: (B) Tetrapodomorph Fishmentioning
confidence: 99%
“…Therefore, Panderichthys and Tiktaalik are interpreted as lacking a pectoral process, while that of the Catskill humerus is weakly developed, a position followed by Ahlberg (2011). This means that the 'pectoralis process' in Rhizodus, Strepsodus (Andrews & Westoll, 1970b;Jeffery, 2001) (black arrow, Fig. 9D), Sauripterus (Davis et al, 2004) and Sterropterygion (Rackoff, 1980), located at the preaxial end of the ventral humeral ridge, was probably misidentified (i.e.…”
Section: (B) Tetrapodomorph Fishmentioning
confidence: 99%
See 3 more Smart Citations